ANALISIS KINERJA SISTEM KOMUNIKASI SERAT OPTIK DENGAN MENGGUNAKAN METODE POWER LINK BUDGET DAN RISE TIME BUDGET PADA PT.TELKOM ( Studi Kasus Link Batusangkar – Lintau ) - Okses Efriyanda; Delsina Faiza; Ahmaddul Hadi (Universitas Negeri Padang, 2014)
This study aims to analyze the performance of a fiber optic communication system to link Batusanggkar – Lintau PT.Telkom. The tools used are the OTDR and optical power meter. Type of optical fiber used is an optical fiber with G.655. Core optical fiber studied as much as 8 cores. The average attenuation of each core generated based on the OTDR is 0.22139 dB/km, while the average attenuation measurements of each core based power meter that is 0.236075 dB/km. Average attenuation OTDR and power meter still below the values ​​calculated in reference to the ITU-T standard is 0.285448 dB/km. Results of power link budget calculations on each core with a cable length of 34,665 km with total average attenuation of each core 9.84019 dB and output power received is -8.51019 dBm receiver, then the value of the link power budget calculations compared with Rx transmitting device sensitivity (-27 dBm = 0.002 mW), where the value of the calculation is smaller than the Rx sensitivity. It can be concluded that the performance of an optical fiber communication system to link Batusanggkar - Lintau which has worked well and normal. While the rise time budget analysis results indicate that the value of the overall system rise time exceeds the maximum standard of 35% RZ bit period of 10 Gbps bit rate is 35 ps (53,689 ps> 35 ps). Keywords: OTDR, Power Meter, Core, Link Power Budget, Rise Time Budget